Improving Students' Concept Understanding Ability Through E-Modules Based on Concept-Rich Instruction Assisted by Live Worksheets - Siti Patunah; Hanipa Hanipa; Aldi Pranata (Departemen Pendidikan Matematika, FPMIPA, UPI, 2024)
Teacher-centered mathematics learning and teaching materials that do not support contextual problems cause a low level of students' ability to understand concepts. The purpose of this study is to produce and determine the quality of Concept-Rich Instruction (CRI)-based e-module development products assisted by direct worksheets. The research method used is the research and development method (Research and Development) and the model used is the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. Data analysis techniques were obtained from validation questionnaires (validated by a team of materials and design experts), practicality questionnaires (teachers and students), student response questionnaires and student concept comprehension tests used to see effectiveness. The results of this study were in the form of e-modules based on Concept-Rich Instruction (CRI) assisted by direct worksheets to improve students' understanding of concepts and it was found that e-module products were proven to be valid, practical and effective with a material validity level of 93% (very valid), design validity of 88% (very valid), practicality by teachers 89.3% (very practical), practicality by students 88.28% (very practical), and effectiveness (student response questionnaire) 85.72% (very effective). Based on the results and discussion, it was found that e-module products based on Concept-Rich Instruction (CRI) assisted by direct worksheets to improve students' concept understanding can improve students' concept comprehension skills.